The Relevance of Heideggerian’s Concept of «cura» in the Ecological Debate - Caballero Bono, José Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2019)
This article studies the use of Heideggerian concept of «Sorge» for a philosophy of ecology. First, analyze the translations of «Sorge» in Spanish language. A critical analysis chooses the concept of «cura». Second, present the meaning of «cura» in Heidegger. Third, show the possibilities of the concept «cura» for an ecological reflection: an interpretation of the work of Hans Jonas, The Imperative of Responsibility, is made here as an ecological derivation of the Heideggerian «cura». In this way, «Dasein» is affirmed as a place of connection between man and nature.